2007
DOI: 10.1590/s0100-39842007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-sonografia mamária: avaliação dos critérios ecográficos na diferenciação das lesões mamárias

Abstract: OBJECTIVE: Breast cancer is one of the most important causes of death in women. The association of different diagnostic methods has been successfully employed as a means to enhance early diagnosis. In this scenario, the interventional and diagnostic breast ultrasound has played a significant role. This study has two main objectives: to identify echographic criteria related to benignancy and malignancy and to analyze echographic characteristics, evaluating their role as malignancy predictors. MATERIALS AND METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
1
14
1
2
Order By: Relevance
“…Nodule margins represented a relevant criterion in the differentiation between benign and malignant lesions, with a NPV ranging between 82.4% and 80.3% for circumscribed margins, not very different from the findings reported by Calas et al (23) , who had observed a NPV of 97% for circumscribed lesions. In the present study, the PPV for noncircumscribed margins ranged between 52.4% and 44.9%, differently from the NPV described by Calas et al (23) , corresponding to 70.4%.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Nodule margins represented a relevant criterion in the differentiation between benign and malignant lesions, with a NPV ranging between 82.4% and 80.3% for circumscribed margins, not very different from the findings reported by Calas et al (23) , who had observed a NPV of 97% for circumscribed lesions. In the present study, the PPV for noncircumscribed margins ranged between 52.4% and 44.9%, differently from the NPV described by Calas et al (23) , corresponding to 70.4%.…”
Section: Discussioncontrasting
confidence: 63%
“…Antiparallel nodule orientation in relation to the skin axis presented a high PPV (72.3%). In the study developed by Calas et al (23) a PPV of 57.6% has been observed.…”
Section: Discussionmentioning
confidence: 88%
“…In several studies in the literature, morphological criteria with higher PPV in relation to nodules were spiculated margins, followed by irregular shape ranging from 70% to 92% (14,(23)(24)(25)(26) . For irregular and spiculated nodules, the authors have found PPV of 94.28%, a value similar to those reported in the literature.…”
Section: B Amentioning
confidence: 99%
“…This observation is compatible with the sonographic findings where most of times, the tumor recurrences presented heterogeneous texture (Table 1), while the benign lesions and hyperplasias presented hypoechogenicity and predominantly homogeneous texture. This is a relevant finding, considering that the quantitative analysis of complex or hypoechoic echotextures may present a low positive predictive value (26,27) , so emphasizing the relevance of the quantification.…”
Section: Discussion Of the Texture Parameters Involved In The Differementioning
confidence: 86%